Full Coverage Prediction with UTD and GO model - Arık, Eray; Tabakcıoğlu, Mehmet Barış (Bursa Teknik Üniversitesi, 2018)
In order to improve the quality of service in UHF broadcasting systems, extracting of coverage map is so important. Coverage map is drawn after electric field is predicted by means of Uniform Theory of diffraction (UTD) and Geometrical optic (GO) models. In urban areas, direct, reflected and diffracted fields are used to generate the coverage map. In this study, coverage maps are extracted for two different scenarios.